Adversity Quotient Sebagai Prediktor Kemampuan Komunikasi Matematis Siswa Madrasah Ibtidaiyah - Maulani, Leni (Moderasi : Journal of Islamic Studies, 2024)
This study aims to determine whether the Adversity Quotient (AQ) can be a predictor of the mathematical communication ability of fifth-grade students at Madrasah Ibtidaiyah in the topic of statistics. AQ is an individual's ability to respond to and overcome difficulties, measured using the Adversity Response Profile (ARP) questionnaire consisting of 40 negative statements based on Stoltz's theory (2004), which includes four indicators: Control (C), Ownership (O₂), Reach (R), and Endurance (E). The AQ score range is 40–200. Meanwhile, students' mathematical communication skills are measured through an essay test consisting of eight questions based on indicators from Sumarmo (2014). This study uses a non-experimental quantitative approach with a correlational design. The residual normality test showed a significance value of 0.299, indicating that the residuals are normally distributed. Simple linear regression analysis resulted in the regression equation Ŷ = -8.463 + 0.194x, with a coefficient of determination (R²) of 30.7%. The ANOVA test showed a significance value of 0.001 (< 0.05), indicating a significant effect of the Adversity Quotient on mathematical communication ability. These results indicate that the Adversity Quotient can be used as a predictor in identifying students' mathematical communication ability at MI, particularly in the topic of statistics